2006
DOI: 10.1158/1541-7786.mcr-05-0085
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cell Death Induced by Histone Deacetylase Inhibitors in Androgen Receptor–Positive Prostate Cancer Cells

Abstract: Histone deacetylase inhibitors (HDACI) are potential therapeutic agents that inhibit tumor cell growth and survival. Although there are several publications regarding the effects of HDACIs on prostate cancer cell growth, their mechanism(s) of action remains undefined. We treated several human prostate cancer cell lines with the HDACI trichostatin A and found that trichostatin A induced cell death in androgen receptor (AR) -positive cell lines to higher extent compared with AR-negative cell lines. We then disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 39 publications
4
59
0
Order By: Relevance
“…17 We previously described redistribution of p53 from the cytosol to the Triton X-100-insoluble fraction, which consists of lipid rafts, cytoskeletal proteins, and chromatin in response to TSA treatment in LNCaP. 15 DU145 also demonstrated down regulation of p53 in the cytosol in response to TSA and this down regulation was inhibited in DU145 siCaspase-2 (Taghiyev AF, Guseva NV, Rokhlin OW, Cohen MB. unpublished data).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…17 We previously described redistribution of p53 from the cytosol to the Triton X-100-insoluble fraction, which consists of lipid rafts, cytoskeletal proteins, and chromatin in response to TSA treatment in LNCaP. 15 DU145 also demonstrated down regulation of p53 in the cytosol in response to TSA and this down regulation was inhibited in DU145 siCaspase-2 (Taghiyev AF, Guseva NV, Rokhlin OW, Cohen MB. unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…At the same time, using a caspase-9 specific inhibitor Z-LEHD-fmk and caspase-9dn expressing DU145 showed an 85% decrease of caspase activity after TSA treatment compared to control. 14,15 It is possible, that caspase-8 initiated caspase cascade occurs via DISC formation due to altered expression of TNF-family receptors and/or ligands. There are several publications indicating upregulation of TNF family receptors and ligands after HDI treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have indicated that inhibitors of HDACs differentially induce apoptosis in prostate cancer cells (13,14). Importantly, treatment of LNCaP cells with trichostatin A (TSA) is shown to induce cell death through downregulation of the transcription of the androgen receptor (AR) gene (14).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in vitro have shown that TSA can be used in the treatment of ovarian cancer, pancreatic endocrine carcinoma, prostate cancer, etc [16][17][18] . The results of this study focusing on the effect of histone deacetylase inhibitor, trichostatin A (TSA) on the proliferation of gallbladder carcinoma cell line (Mz-ChA-l cell line) and cholangiocarcinoma cell lines (QBC939, KMBC and OZ cell lines) in vivo and in vitro, have demonstrated the value of biotherapy for biliary tract cancer with TSA.…”
Section: Introductionmentioning
confidence: 99%